2017
DOI: 10.1002/app.45952
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the gas separation performance of fluorinated and sulfonated PEEK membranes by incorporation of zeolite 4A

Abstract: Mixed matrix membranes (MMMs) containing fluorinated‐sulfonated poly(ether ether ketone) (F‐SPEEK) and zeolite 4A filler, were prepared by solution casting. F‐SPEEK with a fixed degree of sulfonation (40%) was used for membrane synthesis. The SEM pictures showed good interfacial adhesion between filler particles and polymer, which was also confirmed by the increase in glass transition temperature of MMMs with increase in filler particles. Pure and mixed gas permeation experiments were carried out to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…• To enhance such interfacial polymer-filler compatibility, the tuning of the nanomaterials prior their embedding into the polymer matrix has been one of the main fields explored in MMM fabrication (Seoane et al, 2015;Rosyadah Ahmad et al, 2016;Shan et al, 2016;Tahir et al, 2018). This scope comprises modification of the chemical properties of filling materials, which may enhance such polymer-filler interaction and hence promote better GS performance.…”
Section: Protocols For Mitigating Non-desired Interfacial Defectsmentioning
confidence: 99%
“…• To enhance such interfacial polymer-filler compatibility, the tuning of the nanomaterials prior their embedding into the polymer matrix has been one of the main fields explored in MMM fabrication (Seoane et al, 2015;Rosyadah Ahmad et al, 2016;Shan et al, 2016;Tahir et al, 2018). This scope comprises modification of the chemical properties of filling materials, which may enhance such polymer-filler interaction and hence promote better GS performance.…”
Section: Protocols For Mitigating Non-desired Interfacial Defectsmentioning
confidence: 99%
“…11,12 In addition, uorination of this polymer (F-SPEEK) has been employed for enhanced gas separation. 13,14 Inan et al 15 also produced SPEEK/poly vinylidine uoride polymeric blends and demonstrated improved chemical stability and methanol separation properties, to the cost of lowered water uptake and proton conductivity with increased uorocarbon content. Other examples of promising polymer membranes currently under development include poly(arylene ether sulfone) derivatives [16][17][18] as well as multi-block polymers, [19][20][21] where chemical modications such as sulfonation are also considered.…”
Section: Introductionmentioning
confidence: 99%
“…The cohesive energy required to activate the fracture within the composite coating is higher than the adhesive energy at the layers interface. This could be attributed to a greater affinity of the S‐PEEK with the zeolite filler with respect to the metal substrate 48 . This cohesive behavior is inhibited at large filler content, where the crack activation and propagation occurs either within the coating or at the coating/substrate interface.…”
Section: Resultsmentioning
confidence: 99%